EFEKTIFITAS METODE WISH AND DRIVE TERHADAP ENGETAHUAN, SIKAP DAN NIAT PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) PADA WANITA USIA SUBUR - Intan Puspa Rahayu; Desi Widiyanti; Eliana Eliana (JURNAL PENELITIAN TERAPAN KESEHATAN, 2020)
Abstract: Cancer-related morbidity in the world in 2012 was 14.1 million with a death rate of 8.2 million. Indonesia ranks second after breast cancer with new cases of cervical cancer around 20,928 and the percentage of deaths from cervical cancer by 10.3%. The incidence of cervical cancer in Bengkulu Province is 0.8% of 16 / 100,000 women in Indonesia. Puskesmas Tumbuan including Puskesmas with low coverage of VIA Test. Educating the wish and drive method is one of the efforts in increasing VIA coverage. The objective of this research is to know the effect of the education of wish and drive method on intention of VIA Test at fertile age woman at Tumbuan puskesmas 2017. The research design used quasi experiment, two group pre and posttest design, population of woman of age 30-50 years old, sampling with purposive sampling counted 36 WUS. Primary data collection using questionnaire tool. Data analysis used univariate test and bivariate different test.The result of this research is knowable that the education of wish and drive method has an effect on knowledge, attitude and intention toward VIA Test with p value (p = 0.000, p = 0.000, p = 0.009). It is hoped that the education of wish and drive method can be continued in the agenda of Puskesmas activity on early detection of cervical cancer by VIA method. Keywords : VIA Test, education of wish and drive methods